Analisis Serum Iron, Hemoglobin dan Sel Darah Sebagai Penanda Toksisitas Karbon Monoksida Pada Tikus yang Dipapar Rokok Filter - Havida Widyastuti; Budi Santoso; Mudyawati Kamaruddin; Widyastuti, Havida (Journal of Health, 2025)
Carbon monoxide (CO) is a harmful substance when inhaled in excessive amounts, leading to cellular distortions. The presence of CO in the blood forms carboxyhemoglobin, which reduces the overall oxygen-carrying capacity, potentially resulting in hypoxia. In response to hypoxia, the body compensates by stimulating the production of new erythrocytes and increasing iron levels. This study aims to analyze serum iron, hemoglobin, and blood cell levels as sensitive markers of CO toxicity. The study employed a true experimental post-test-only control group design with 25 rats divided into five groups that is one negative control group that not exposed to cigarettes and four treatment groups (1, 2, 3, and 4), which were sequentially exposed to filter cigarettes at rates of 2, 4, 6, and 8 cigarettes per day for 14 days. Spectrophotometric and impedance analysis methods were employed. Data analysis was performed using SPSS with post hoc tests. This studi shows that  significant increase compared to the negative control in hemoglobin was observed in all treatment groups, serum iron in group 4 (181.10 µg/dL), erythrocytes in group 4 (13.04x1012cells/L), and leukocytes in groups 2, 3, and 4 with mean levels of (12.4x109cells/L; 14.03x109cells/L; 15.09x109cells/L), while platelets showed no significant increase compared to the negative control. The study concluded that hemoglobin serves as one of the most sensitive markers of toxicity, demonstrating significance even at the lowest dose of cigarette smoke exposure.